A developmental model for alcohol use disorders in Swedish men. Issue 13 (22nd July 2016) - Kendler, K. S.; Ohlsson, H.; Edwards, A. C.; Sundquist, J.; Sundquist, K.
Abstract : Background: Alcohol use disorder (AUD) is a classic multifactorial syndrome and it is critical to understand the diversity of the relevant risk factors and how they inter-relate over development. Method: We examined 21 risk factors for AUD in four developmental tiers reflecting (i) birth, (ii) childhood and early adolescence, (iii) late adolescence, and (iv) early adulthood in 47 414 Swedish men of whom 3907 (8.2%) were registered for AUD at or after age 25 with a mean length of follow-up of 33.9 (6.6) years. Structural equational model fitting was performed using Mplus. Results: The best-fitting model provided a good fit to the data and explained 23.4% of the variance in AUD. The five strongest predictors were: externalizing behaviors, criminal behavior, father's alcohol consumption, genetic risk, and low educational attainment. Two developmentally early familial/genetic risk factors had substantial direct paths to AUD: father's alcohol consumption and genetic liability. Other broad developmental pathways to risk for AUD were evident: externalizing, psychosocial and internalizing. Overall, the externalizing pathway to AUD was the strongest. However, these pathways were substantially interwoven over time such that risk factors from one domain were commonly predicted by and/or predicted risk factors from the other broad domains of risk. Conclusion: AUD in men is an etiologically complex syndrome influenced by familial-genetic, psychosocial, internalizing, and especially externalizing risk factors that act and interact over development and have complicated mediational pathways.